How is advanced melanoma treated in the Public Health System in Brazil: a call for change. - Kaliks, Rafael Aliosha; Santos, Andre Marques; Matos, Tiago Farina; Holtz, Luciana (Brazilian Journal of Oncology, 2019)
Introduction: Treatment of advanced melanoma has been revolutionized in the last decade. The adoption of new treatments is necessary in order to offer significantly longer survival. Objective: To evaluate how patients are being treated for advanced melanoma at the Public Health System in Brazil. Methods: We evaluated the Authorization of Ambulatory Care Procedure (APAC) related to all patients treated for advanced melanoma between January 2015 and December 2017. We grouped treatments according to their reported efficacy as being inadequate, minimally effective, moderately effective or effective treatments. We evaluated treatments given according to the efficacy, variety of treatments in first line and duration of overall treatment. Results: We analyzed 10,843 APACs, related to the treatment of 4,338 patients. Patients were 57% male, 43% female, 72% were older than 50 years of age. The median number of APACs filled per patient was 2 (ranging from 1 to 15). The mean of different types of treatment prescribed to individual patients was 1.22 (1 - 5). We identified 19 different treatment protocols used as first line, of which 11 consisted of single drug and 8 of drug combinations. Over the two-year period, 3,097 (88%) and 281 (8%) patients initiated treatment with a minimally effective or moderately effective regimen, respectively. Only 0.4% of patients initiated their treatment with an effective therapy. The average length on any treatment was six months. Conclusion: More than 98% of patients treated between 2015 and 2017 for advanced melanoma at the Public Health System in Brazil received minimally effective treatments.
Keywords: Melanoma; Combined modality therapy; Health systems; Unified health system; Neoplasm metastasis.